Never Too Late The Importance of Adequate Physical Activity and Exercise in Senior-Aged Adults - Coleman, Jayda S (My University, 2024)
Exercise for older adults is significant and valuable for many reasons. Regular exercise helps older adults maintain muscle strength, joint flexibility, and cardiovascular health. This can reduce the risk of falls, fractures, and other injuries. Exercise can help prevent or manage chronic conditions such as heart disease, diabetes, arthritis, and osteoporosis. It can also improve immune function, reducing the risk of infections. Physical activity is linked to improved mood and mental well-being. It can help relieve symptoms of anxiety and depression, enhance cognitive function, and promote better sleep. By improving strength, balance, and mobility, exercise can help older adults maintain their independence and perform activities of daily living for longer. Research suggests that regular exercise is associated with a longer lifespan and a higher quality of life in older adults. Weight-bearing exercises and resistance training can help maintain bone density and reduce the risk of osteoporosis and fractures. Overall, exercise is crucial in promoting health and well-being in older adults, helping them live longer, healthier, and more fulfilling lives.
Keywords: Senior-aged adults, exercise promotion and education, benefits of physical activity